PENDIDIKAN RAMAH ANAK USIA SEKOLAH DASAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER - Hendriana Monalisa; Ratih Dwi Yulianti Rahayu (Universitas Sarjanawiyata Tamansiswa, 2019)
The study aimed to improve the friendly education of elementary school children using the cooperative learning model, one of Numbered Head Together (NHT). This research method uses a qualitative approach to describe and outlines a friendly education for elementary school-aged children using the cooperative learning model numbered head together (NHT). What will be described is the ability of teachers to be fair to children, not discriminating children, showing affection to all children, and giving more attention to children who do not understand about learning, so that children feel safe, comfortable, not anxious and feel confident during the learning process. This research method uses two variables, namely the independent variable and the dependent variable. The independent variable of this study is that one type of cooperative learning model is the numbered head together (NHT) type, while the dependent variable is child-friendly education. Implementation of the friendly education of elementary school-aged children is an inseparable part of a learning model, one of which is the Numbered Head Together (NHT), a learning model. Constraints in implementing child-friendly education using this type of Numbered Head Together (NHT) learning model, namely environmental influences. Advice to be demonstrated to the school that should consider the condition of class, and be able to be fair, always give love, and feels safe and comfortable to the child.